Hardiness as a Mediator between Daily Life Hassles and Psychological Well-being among Adolescents - Saeed, Bushra; Hanif, Rubina (Pakistan Journal of Humanities and Social Sciences, 2024)
Adolescents face various challenges in their lives and family hardiness not only work as a coping construct but also contribute to the wellbeing of adolescents in facing daily life hassles. Hence, there is a need for further evaluation of family hardiness in reducing the impact of stress and amplifying psychological well-being in adolescents. Present research suggested evaluation of the mediating role of family hardiness between daily life hassles and psychological well-being. A convenient sample of 250 adolescents (aged 11 to 21 years), from two cities of Pakistan, was administered with indigenous Daily Life Hassles, Family Hardiness Index (FHI), and Psychological Well-being Scales. Research questions of the present study were evaluated through the procedures of PROCESS and Statistical Package for Social Sciences (SPSS) version 21. Findings of the present study revealed that family hardiness has a mediating role between daily life hassles experienced and appraised as stressful by adolescents and their well-being, and adolescents with enhanced well-being also reported daily hassles less frequently and appraised less stressful. Similarly, significant number of adolescents with enhanced well-being also reported enhanced levels of family hardiness. Findings of the present study emphasize the critical roles of hardiness as buffer against perceived stress in adolescents and also its role an amplifier for well-being in adolescents.